Blood‐derived compounds can efficiently prevent iron deficiency in the grapevine. (11th November 2014) - López‐Rayo, S.; Di Foggia, M.; Bombai, G.; Yunta, F.; Rodrigues Moreira, E.; Filippini, G.; Pisi, A.; Rombolà, A.D.
Abstract Background and Aims The present study investigated the effectiveness of bovine blood (BB)‐based products, compared with that of the widely used iron ethylenediaminedi‐(2‐hydroxyphenylacetic) acid (Fe‐EDDHA) synthetic chelate, in iron nutrition of grapevine graft combinations and rootstocks grown under different controlled conditions. Methods and Results In experiments under nutrient solution utilising rhizoboxes and pots, the effect of iron application treatments was evaluated through biometric and chlorophyll index measurements, leaf nutrient concentration and root scanning electron microscopy. Conclusions The bovine blood compounds improved iron nutrition of the grapevine similar to or better than Fe‐EDDHA and enhanced root growth. Significance of the Study The experimental evidence indicates that BB‐based products represent a sustainable alternative to synthetic chelates as Fe fertilisers.